Enhancing Product Sales through the Implementation of an E-Commerce-Based Marketing System - Putri Prasetyaningrum; putry wahyu setyaningsih; Ozzi Suria; Ibnu Rivansyah Subagyo (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
This service project is titled